Observing the Existence of the Constitutional Court Addresses the Evolving Dynamics and Challenges of the Legal System in Indonesia - Nining (Yayasan Sinergi Kawula Muda, 2023)
The evolution of the legal paradigm in Indonesia after the reform era reflects efforts to move towards a more democratic legal system that respects human rights. The presence of the Constitutional Court (MK) as a constitutional judicial institution has had a significant impact on the consistency of legislation and the role of the Constitutional Court in addressing the extent of the development, dynamics, and challenges of the Indonesian legal system at present. This article will discuss and examine, first, the extent to which the Constitutional Court actively contributes to improving the quality of Indonesian law, and second, whether Constitutional Court decisions can create legal precedents that can be used as references in establishing new laws. The lack of access to justice in various layers of society requires improvements in the context of creating a more inclusive and efficient legal system. The decisions of the Constitutional Court are final and binding, and the mechanism of checks and balances needs legal reconstruction regarding the regulation of the nature of Constitutional Court decisions by explicitly emphasizing the word